Implementasi Project-Based Learning melalui Aktivitas Pembuatan Ice Cream Putar pada Siswa Sekolah Dasar - SUMARNI, Sumarni; Purwati, Sasi; Febrianti, Regita; Suciyani, Rini; Fadillah, Saefi; Anggraeni, Sarah Agid (LPPM Universitas Terbuka, 2024)
One of the learning activities in campus teaching activities is using the project-based learning model. This research aims to describe good practices, challenges and good experiences from implementing learning activities using project-based learning in rotating ice cream making activities. This research is qualitative research, with a descriptive approach. The subjects of this research were 20 students in class IV of one of the elementary schools in Cirebon district. Data collection was carried out through observation, interviews and documentation of learning activities. Data analysis uses data triangulation techniques which include data reduction, data presentation and drawing conclusions. The results of research from learning in Natural and Social Sciences (IPAS) subjects using project-based learning in the activity of making rotating ice cream, good practices were obtained: students were able to produce rotating ice cream products, students understood the concept of Change of Form material, namely the concept of